Opposite effects of acute kidney injury on pharmacokinetics of renally and hepatobiliary excreted drugs. (29th May 2018) - Giri, Poonam; Delvadia, Prashant; Joshi, Vipul; Trivedi, Priyal; Srinivas, Nuggehally R
Aim: Influence of cisplatin-induced acute kidney injury (AKI) on the pharmacokinetics of ciprofloxacin/fasiglifam was investigated.Methods: Normal and AKI rats received oral/intravenous doses of 5 and 1 mg/kg for ciprofloxacin and 3 and 1 mg/kg for fasiglifam, respectively. Plasma samples were subjected to LC–MS/MS analysis, followed by pharmacokinetic analysis. Liver S-9 fractions were used for stability assessment.Results: Regardless of intravenous/oral dosing, ciprofloxacin concentrations increased in AKI relative to normal rats. Oral bioavailability of ciprofloxacin was 79/24% in AKI/normal rats. With fasiglifam, pharmacokinetics was not altered in AKI versus normal rats after intravenous dosing. However, oral dosing showed 25–36% lower exposure in AKI rats. Liver S-9 fractions obtained from AKI/normal rats showed metabolic stability.Conclusion: AKI rats showed enhanced/decreased bioavailability of ciprofloxacin/fasiglifam.